PEMBIAYAAN MULTI JASA MENGGUNAKAN AKAD IJARAH DI PT. BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) AL FALAH BANYUASIN - Rama Riyaldi; Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
This research discusses how Multijasa Financing uses the Ijarah contract at PT. Sharia People's Financing Bank (BPRS) AL Falah Banyuasin. This research method is interview. The results of this research are: Multi-Service Financing Mechanism using the Ijarah contract is as follows: The bank acts as a provider of funds in Multi-service transactions with customers. The bank is obliged to provide funds to realize the provision of rental objects ordered by customers. Refund of bank funds can be made in the form of receivables or in the form of debt.